HomeCoRe system for telerehabilitation in individuals at risk of dementia: A usability and user experience study - Bernini, Sara; Panzarasa, Silvia; Quaglini, Silvana; Costa, Alfredo; Picascia, Marta; Cappa, Stefano F.; Cerami, Chiara; Tassorelli, Cristina; Vecchi, Tomaso; Bottiroli, Sara (Frontiers in Medicine, 2023)
Background Telerehabilitation has enabled a broader application of cognitive rehabilitation programs. We have recently developed HomeCoRe, a system for supporting cognitive intervention remotely with the assistance of a family member. The main goal of the present study was to determine usability and user experience of HomeCoRe in individuals at risk of dementia and in their family members. The association between subjects’ technological skills and main outcome measures was evaluated as well. Methods Fourteen individuals with subjective cognitive decline (SCD) or mild neurocognitive disorder (mNCD) were recruited to participate in this pilot study. All participants received a touch-screen laptop implemented with the HomeCoRe software. The intervention consisted of 18 sessions and included a patient-tailored adaptive protocol of cognitive exercises. Usability was assessed in terms of treatment adherence and participants’ performance across sessions; user experience via self-reported questionnaires and a descriptive diary. Results Usability and user experience were overall satisfactory and suggested usability, pleasantness, and high motivation while using HomeCoRe. Technological skills correlated only with the perceived ability to start and/or perform exercises autonomously. Discussion These results, although preliminary, suggest that the usability and user experience of HomeCoRe are satisfactory and independent of technological skills. These findings encourage wider and more systematic use of HomeCoRe to overcome the current limitations of in-person cognitive rehabilitation programs and to reach more individuals at risk of dementia.